EFEKTIVITAS MODEL KONSELING BEHAVIORAL PAVLOV DENGAN TEKNIK CLASSICAL CONDITIONING UNTUK MENINGKATKAN SELF ACHIEVEMENT - Azhar, Dimas; Suranata, Kadek; Dharsana, I Ketut (Universitas Pendidikan Ganesha, 2019)
This study aims to know: Effectiveness of behavioral counseling i. f. Pavlov with classical conditioning techniques through lesson study to improve self achievement. This research includes